Contexto social y pastoral que da origen a la teología de la liberación en América Latina entre 1955 y 1992. (2016)
Starting from the complex discussion on society and theology, this paper attempts to address key socio-pastoral factors that took place in Latin America between the years of 1955 to 1992, as part of justification for the initiation and subsequent expansion of the "Theology Liberation ". The references that are located are, from the magisterium of the Catholic Church, historians, to own the theology of liberation, along with exponents, without being in this stream, have in his speech contextual similarity and pastoral concern sources. The analysis is undertaken must be considered as the start mark one of the strong current discussions: the Church in today's society.